Fundamentals of biostatistics - Rosner, Bernard (Brooks/Cole, Cengage Learning, 2011)
Leads the reader through the methods, techniques, and computations necessary for success in the medical field. Every new concept is developed systematically through completely worked out examples from current medical research problems.